Assessing the Impact of Digital Transformation on Regulatory Processes and Systems Compared to Traditional Paper-Based Processes at the Egyptian Drug Authority - Soliman, Rania AA (AUC Knowledge Fountain, 2025)
In the past several decades, the rate of scientific and technological advancements in drug development and digital fields have been extraordinary. Internet of Things and block chain technologies are currently viable in the mature cloud computing industry, these transformative examples contrast starkly with the current pharmaceutical regulatory submission, review, and approval process of the EDA. However, with the emergence of initiatives that aim to improve and expedite regulatory decision-making, there is a promising future ahead. These initiatives, if successful, will not only transform the current transactional structure but also leverage scientific and technological advances to deliver patient-centric therapies. This radical transformation will be challenging for regulatory authorities, such as EDA, and corporate sponsors, and progress will be linear. Acknowledging the complexity of these challenges the pressing need for rigorous research to develop effective frameworks that tackle design challenges, legal compliance issues, and technological integration within Egypt’s pharmaceutical regulatory landscape. The COVID-19 pandemic has highlighted the urgent necessity for swift, secure, and efficient communication channels between regulatory agencies and industry stakeholders, facilitating timely decision-making and accelerating global approvals. This reality necessitates a reevaluation of how digital platforms are utilized in the pharmaceutical and medical device sectors. The evolving regulatory landscape mandates the harmonization of data requirements through integrated digital solutions, backed by adequate resources. It is essential to foster trust through secure information-sharing platforms and harness AI to amplify organizational functions, all while effectively managing the human factors associated with technological change. These concerted efforts are designed to significantly improve efficiency, safety, transparency, and public value across healthcare regulation and public administration. Research Design Summary To comprehensively evaluate the impact of digital transformation on regulatory frame work, a mixed-methods approach was employed: Quantitative Data Collection: Descriptive data have been collected from all applications submitted over the past four years (November 2019 – October 2023), sourced directly from the EDA’s marketing authorization department. This data is critical for analyzing trends in process efficiency over time. Qualitative Data Collection (Survey): An online survey was meticulously developed by adapting questions from existing validated surveys. Its objective is to assess user experiences among EDA employees and clients engaged with the digital platform. This robust research methodology enables a thorough understanding of how digitization has decisively impacted the efficiency of regulatory processes and stakeholder satisfaction within the medical device regulation framework governed by EDA regulations. The analysis highlights strong performance in data security and overall satisfaction but identifies areas for improvement in responsiveness, timeliness, and ease of issue resolution. These areas warrant attention to enhance user experience and maintain customer and employee confidence. This study has several strengths, including a very high response rate, which was achieved through significant efforts to ensure that participants clearly understood the survey questions. This involved designing the questions to be clear, understandable, and accessible, as well as providing additional explanations and clarifications where necessary. By focusing on participant comprehension, the study minimized confusion and encouraged more accurate and complete responses. This, in turn, contributed to the high response rate and made the results more comprehensive for stakeholders, including both EDA staff and customers. The findings can significantly enhance the EDA's ongoing modernization efforts, increasing the study’s relevance and applicability. The study offers actionable recommendations aimed at improving the EDA’s regulatory processes and aligning them with global best practices. Moreover, it establishes a connection between the fields of digital transformation and regulatory science, offering a multidisciplinary perspective. The study also includes input from key stakeholders, such as regulators and industry representatives, reflecting a comprehensive understanding of the issue from various viewpoints. Furthermore, this research aligns with the international movement towards the digital transformation of regulatory agencies, as seen in the efforts of organizations like the FDA and the EMA. By addressing this relatively new topic, the study opens up opportunities for further research on related subjects, such as the role of artificial intelligence and big data in regulatory reform. The study has limitations that should be acknowledged. Firstly, the qualitative component could have been more detailed, specifically in investigating the quality of data available post-digitalization and its impact on decision-makers. This exploration could have included sharing experiences with other government departments that underwent digitization before the EDA department or conducting comparative studies to identify overlooked gaps and learn from those experiences. Additionally, the study may not have fully addressed organizational resistance and cultural challenges associated with digital transformation. It is also important for the study to explain the role of legislative reforms in establishing a more flexible regulatory framework. Lastly, the influence of broader factors, such as cultural changes and alignment with global regulatory trends, may require further research.